EFFECT OF SPRAYING WITH BENZYLADENINE AND PHOSPHORUS ON THE GROWTH, FLOWERING AND CONTENT OF ACTIVE COMPOUNDS OF CALENDULA OFFICINALIS - Nawal M. Alwan; Sundus A. AL-Rahman; Sadiq M. Sadiq (The Iraqi Journal of Agricultural science)
This study aimed to investigate the effect of spraying benzyladenine and phosphorus on growth, flowering, and medicinal active compound content of Calendula officinalis cultivar "Bon Bon” under wooden shade conditions. The experiment was conducted using a factorial experiment within Randomized Complete Block Design with three replicates, examining two factors: benzyladenine at three concentrations (0, 50, and 100 mg L-1) and phosphorus at three concentrations (0, 2.5, and 5 mg L-1). The results indicated that benzyladenine (BA2) and phosphorus (P2) treatments significantly enhanced vegetative and floral growth, including plant spread, height, leaf number, branch number, and both fresh and dry weights. Additionally, these treatments improved floral characteristics such as flowering duration, number of flowers, flower diameter, peduncle length, peduncle diameter, fresh and dry flower weights, and flower longevity on the plant.